Maximal aerobic power-cadence relationship estimation in national level under nineteen cyclists from in-situ data - Bertron, Y.; Bowen, M.; Leo, P.; Samozino, P.; Pacot, A.; Hintzy, F.; Morel, B. (Journal of Science and Cycling, 2022)
For any given duration, the cyclist performance capacities can be determined with based on a power profile i.e. mean maximal power (MMP). Power is a product of torque and cadence, and maximal efforts in cycling can be modeled by a polynomial relationship between maximal power and the optimal cadence. The objective of this research is to explore the torque- and power - cadence relationship for MMP 5-min (as a surrogate of maximal aerobic power (MAP MMP 5-min data for al cadences between 60 and 120rpm were analyzed accordingly. The goodness of fit was excellent (r² = .90 [.82-.94]). The even-odd days intraclass correlation coefficient (ICC) were very high for Topt and Pmax (.90 and .94, respectively) and high for Copt (.76). Standard Error Measurement (SEM) was 2.2 N·m-1 for Topt, 4.3 rpm for Copt. and 10.8 W for Pmax. Mean optimal torque values was 42.6 ± 7.0 N·m-1 and the mean optimal cadence - rate was 91rpm ± 8 rpm. The estimated 5-min MMP was 402 ± 40 watts. Thus, the MMP 5-min - cadence modeling is feasible, reliable and produce coherent indicators of cycling performance. This modelling gives important information, such as optimal torque and cadence. Numerous applications for testing, training and racing could be extracted from this innovative approach.